2011
DOI: 10.1038/ajh.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Prenatal Programming of Hypertension by Dietary Protein Deprivation Is Mediated by Fetal Glucocorticoid Exposure

Abstract: Background Prenatal programming by maternal dietary protein deprivation and prenatal dexamethasone result in a reduction in nephron number and hypertension when the offspring are studied as adults. Methods To determine whether prenatal dietary protein deprivation results in a reduction in nephron number and hypertension in offspring by exposure to maternal glucocorticoids, we administered metyrapone to rats fed either a 6% or 20% protein diet to inhibit glucocorticoid production and compared the offspring to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
(56 reference statements)
3
24
0
1
Order By: Relevance
“…Antenatal GC administration has previously been used experimentally to program offspring for adult hypertension , Levitt et al 1996, Ortiz et al 2002, O'Regan et al 2008, Habib & Gattineni 2011. In this study, we demonstrate that administration of the synthetic GC, DEX during the third trimester of gestation results in elevated systolic, diastolic, and mean arterial blood pressure in WKY male rats.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Antenatal GC administration has previously been used experimentally to program offspring for adult hypertension , Levitt et al 1996, Ortiz et al 2002, O'Regan et al 2008, Habib & Gattineni 2011. In this study, we demonstrate that administration of the synthetic GC, DEX during the third trimester of gestation results in elevated systolic, diastolic, and mean arterial blood pressure in WKY male rats.…”
Section: Discussionmentioning
confidence: 61%
“…Further, studies have observed that exposure to high doses of glucocorticoids (GCs) during fetal development, generated either as a consequence of maternal stressors or administered antenatally also reduces birth weight and leads to development of essential hypertension later in life , Drake et al 2007. The role of GCs in the fetal programming of hypertension has been investigated in sheep (Dodic et al 2002), rats , Levitt et al 1996, Ortiz et al 2002, O'Regan et al 2008, Habib & Gattineni 2011, as well as in humans (Karemaker et al 2006). However, the exact mechanisms by which GC-mediated fetal programming of hypertension occurs requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant Sprague-Dawley rats were fed either a control 20% protein diet or a 6% (low) protein diet from the 12th day of gestation until the time of birth using the same protocol as previously described (9,13,14,25). The mothers had all been pregnant previously and were 4 -6 mo of age.…”
Section: Animalsmentioning
confidence: 99%
“…This dosing regimen of MTP has been used effectively in many previous studies. 14,15 At day 1 after birth, the litters were separated by gender, and the body weights of individual pups were recorded. To avoid any undue bias toward selecting heavier or lighter pups, the median body weight per litter per gender was determined, and the 4 females closest to the median body weight for the litter were selected for the study; we chose to focus on only 1 gender (females), since there is a well-known gender effect on lung development.…”
Section: Rat Model Of Mfrmentioning
confidence: 99%